2021
DOI: 10.3390/nu13093205
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Nutrition Intervention in Patients Undergoing Resection for Upper Gastrointestinal Cancer: Results from the Multi-Centre NOURISH Point Prevalence Study

Abstract: Background: Preoperative nutrition intervention is recommended prior to upper gastrointestinal (UGI) cancer resection; however, there is limited understanding of interventions received in current clinical practice. This study investigated type and frequency of preoperative dietetics intervention and nutrition support received and clinical and demographic factors associated with receipt of intervention. Associations between intervention and preoperative weight loss, surgical length of stay (LOS), and complicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
2
9
0
1
Order By: Relevance
“…However overall, the results of the present study are more positive compared to the results of previously conducted surveys of Australian UGI dietitians over 7-10 years ago, which estimated significantly lower outpatient service provision to this population. 4,20 We have previously demonstrated that receiving neoadjuvant therapy was associated with greater likelihood of receiving preoperative dietetics intervention, 3 which is supported by the results of this study demonstrating that the vast majority of sites had dietetics services available in the chemo/radiotherapy settings. However, only 23% and 39% of sites reported having a routine service for the preoperative chemotherapy and radiotherapy settings, respectively, with 31% and 43% for the postoperative chemotherapy and radiotherapy settings.…”
Section: Perioperative Nutrition Servicessupporting
confidence: 60%
See 2 more Smart Citations
“…However overall, the results of the present study are more positive compared to the results of previously conducted surveys of Australian UGI dietitians over 7-10 years ago, which estimated significantly lower outpatient service provision to this population. 4,20 We have previously demonstrated that receiving neoadjuvant therapy was associated with greater likelihood of receiving preoperative dietetics intervention, 3 which is supported by the results of this study demonstrating that the vast majority of sites had dietetics services available in the chemo/radiotherapy settings. However, only 23% and 39% of sites reported having a routine service for the preoperative chemotherapy and radiotherapy settings, respectively, with 31% and 43% for the postoperative chemotherapy and radiotherapy settings.…”
Section: Perioperative Nutrition Servicessupporting
confidence: 60%
“…This is not surprising given that we have previously reported that receiving ≥ 3 preoperative dietetics appointments was associated with lower percentage weight loss because a nutrition care pathway can create a structured approach to nutrition reviews enabling ongoing monitoring and adjustment of intervention. 3 Previous studies have also demonstrated a reduction in malnutrition rates and weight loss when a nutrition care pathway was implemented in an oncology population. 27,28 Receiving care under a pathway/protocol was not associated with receiving preoperative nutrition support, and this could be a result of other health care professionals administering nutrition support such as oral nutrition supplements without the involvement of a dietitian, 3 particularly at sites with limited dietetics services.…”
Section: Nutrition Care Pathways and Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in other major GI surgery settings are needed to further inform the impact of providing MNT in accordance with ERAS guidance on patient outcomes. Nevertheless, studies to date point to a need for greater awareness and practical guidance on how to identify patients at nutritional risk, and provide nutritional prehabilitation and perioperative nutritional support, to address malnutrition as a modifiable risk factor for poor postoperative outcomes [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Achieving nutritional sufficiency reduces malnutrition risk and results in improved clinical outcomes, including shortened LOS and fewer non-elective hospital readmissions. However, structural and institutional barriers to meeting inpatient nutritional requirements and low adherence to ESPEN guidelines occur worldwide [ 23 , 24 , 25 ]. The purpose of this scoping review was to assess the evidence for interrelationships between dietary (energy and protein) intake and clinical outcomes, LOS and hospital readmissions, among adult hospitalised oncology patients.…”
Section: Introductionmentioning
confidence: 99%